Pericardial Effusion due to Infliximab Therapy for Ulcerative Colitis. (6th November 2018) - Mirza, Muhammad; Mirza, Maira; Murugesan, Vagishwari; Olano, Arrel
Abstract : Ulcerative colitis is characterized by ulcers and inflammation of the inner lining of the gastrointestinal tract. Antitumor necrosis factor alpha (anti-TNF alpha) agents such as infliximab are drugs that have been used for the treatment of ulcerative colitis for decades. Infliximab is known to be associated with various adverse effects including anti-TNF alpha induced lupus (ATIL). We present a rare case of a 51-year-old female with pericardial effusion secondary to infliximab therapy for treatment of her ulcerative colitis. Discontinuation of infliximab led to resolution of the pericardial effusion.